Disseminated tuberculosis presented with explicit hypercalcemia: A clinical case report - Seyed Ali Dehghan Manshadi; Nahid Shafiee; Seyed Mohammad Piri; Erfan Naghavi; Maryam Moradi (Clinical Case Reports, 2024)
Key Clinical Message Tuberculosis (TB) is a rare but known reason for hypercalcemia usually in those with underlying conditions such as renal failure, diabetes, or severe anemia. It is essential to consider TB in those with refractory or resistant hypercalcemia. Abstract Hypercalcemia or a calcium level above 10.5 mg/dL can be a manifestation of TB that only became symptomatic in a small percentage of the patients. Patients with underlying diseases such as renal failure are more prone to poor prognosis. It is essential to use anti‐TB drugs besides hypercalcemia standard treatment to maintain a normal calcium level in TB‐related hypercalcemia. In thisstudy, we have presented a young adult with disseminated TB and persistent hypercalcemia who responded finally to anti‐TB drugs.